Biofabrication of a novel bacteria/bacterial cellulose composite for improved adsorption capacity. (October 2019) - Wan, Yizao; Wang, Jie; Gama, Miguel; Guo, Ruisong; Zhang, Quanchao; Zhang, Peibiao; Yao, Fanglian; Luo, Honglin
Abstract: Conventional fabrication of bacterial cellulose (BC) involves treatment with hot NaOH aqueous solutions to remove bacteria (BA). Herein, we report a simpler and cheaper method for the preparation of BA/BC composite without alkalization, which keeps the BA in the nanofibrous BC network. Scanning electron microscopy (SEM) observation showed naturally distributed BA in BC matrix with a tightly entangled structure. Such BA-embedded BA/BC composite exhibited improved mechanical strength and modulus over BC. When used as adsorbent, the BA/BC composite exhibited significantly higher adsorption capacities to Pb(II), Cu(II), Ni(II), and Cr(VI) compared to bare BC. The much higher adsorption capacities of BA/BC are due to the presence of functional groups in the BA, such as amide, which are known to be involved in coordination interaction. This breakthrough strategy not only made the fabrication process simpler and more cost-effective, but also produced a new BC-based adsorbent with improved adsorption capacity to heavy metals.